The Effect of Demographic Character on the Intention of Muslim Consumer Behavior to Shop at Neighbor Store - Jatiningrum, Wandhansari Sekar; Astuti, Amalia Yuli (Department Industrial Engineering, University of Muhammadiyah Malang, 2019)
The purpose of this study is to find out factors related to the behavioral intention of Muslim consumers to shop to neighborhood stores. The Islamic leaders urged the Muslim community to do the social movement to buy for neighborhoods. Its movement is as one form of spirit 212. Spirit of the actions of Muslims in Indonesia in December 2016 through prayer and prayer together to strengthen the kinship of Muslims. Behavioral intention of Muslim consumers to shop to neighborhood store in Yogyakarta is thought to be influenced by attitude, subjective norms, behavioral control, religiousness, and affective commitment to be affiliated with spirit. Consumers have the characteristics of adhering to Islamic principles. Demographic characters are also considered to influence consumer preferences for each factor. Based on the descriptive analysis, the average respondent's answer to religious factor has the highest score compared to other factors. The results of independent t-tests and ANOVA shows that there is a significant difference for the average responses of answers based on gender, which are significantly different based on education, age, occupation, and income.